Combating crime in the sphere of justice: effectiveness of punishment - Mikhail P. Kleymenov; Evgeniy S. Ivanov (Правоприменение, 2019)
The subject. The system of crimes against justice includes four groups of acts, each of which encroaches on a separate group of public relations: crimes that threaten the security of justice, crimes that undermine its justice, crimes that prevent the reasonable adjudication and crimes that execution of judicial decisions.The purpose of the paper is to confirm or refute the hypothesis that the criminal legal response in Russia to groups of crimes in the sphere of justice is not adequate to the degree of their social danger.The methodology. The concept of criminal legal response was chosen as a methodological basis for the analysis of the practice of sentencing. This concept highlights the following types of criminal legal response: lack of response; very weak response – the number of convicts does not exceed 10; weak response – the number of convicts is small, calculated in dozens; adequate response – the number of convicts and penalties correspond to the criminological characteristics of the crime; intensive response – the inevitability of punishment is ensured by the enforcement of rules; punitive response – the norm is applied on the basis of the "letter, not the spirit" of the law; reflexive response – the imposition of punishment "their" in conditions of increased public attention, "resonance" of the case; protest response – judicial practice is in conflict with ill‐conceived legislative innovations.The main results and scope of their application. The weakest, very weak criminal‐legal response or complete absence of criminal‐legal response in the sphere of justice is the most typical in Russia. It is explained by various factors, and the professional lack of competence and the motive of “protection of the honor of the uniform” appear most frequent. The criminal‐legal impact is punitive in relation to the insult of public officer (art. 319 of the Russian Criminal Code). Criminal liability for insulting a public officer is anachronism in the context of full or partial decriminalization of insults in general (art. 130 of the Russian Criminal Code) and beatings (art. 116 of the Russian Criminal Code).Conclusion. The purpose of the study is reached the hypothesis is confirmed partially – in relation to the inadequacy of criminal penalties for insulting a public officer. Decriminalization of art. 319 of the Russian Criminal Code is necessary. Save it in the current Criminal Сode leads to a "witch hunt", in addition to receiving a criminal record every year by thousands of people (that stain not only their biography but also biography of their loved ones). There is art. 5.61 "Insult" in Russian Code of administrative offences. It is proposed to supplement art. 5.61 of the Code of administrative offences of the fourth part: "insulting a public officer during the performance of their official duties" simultaneously with the de‐ criminalization of art. 319 of the Criminal Code.